Lower-dose psycholytic therapy – A neglected approach - Passie, Torsten; Guss, Jeffrey; Krähenmann, Rainer (Frontiers in Psychiatry, 2022)
LSD and similar psychoactive drugs have been used in psychotherapy since 1949, when the first clinical study with lower-dose LSD showed therapeutically relevant effects. This caused an intense interest among psychotherapists and researchers, alike, on an international scale. In 1960, the use of serial lower-dose LSD/psilocybin sessions in a psychoanalytical framework, which was dominant at the time, was named “psycholytic therapy”. Psycholytic therapy was usually conducted in clinical environments, on both an inpatient and outpatient basis. Psycholytic therapy was developed and established over a 15-year period on the European continent, where it was used at 30 clinical treatment centers and by more than 100 outpatient psychotherapists. Psycholytic approaches were employed minimally in North America, where the psychedelic approach (use of one or two high-dose sessions for “personality-transforming mystical experiences”) became the dominant method in use. It is obvious that the leading figure in psycholytic therapy was Professor Hanscarl Leuner in Germany, who laid the ground with his uniquely finegrained analysis of the LSD reaction in 1962 monograph. He was also central in etablishing and distributing psycholytic therapy in Europe and abroad. The article provides comprehensive background information and outlines the essential features of psycholytic therapy. Evidence for the efficacy of psycholytic therapy is reviewed and a case for the inclusion of psycholytic approach in the field of substance-assisted psychotherapy is made.